An Innovative Drug Delivery System Loaded with a Modified Combination of Triple Antibiotics for Use in Endodontic Applications - Ardavan Parhizkar; Hanieh Nojehdehian; Fahimeh Tabatabaei; Saeed Asgary (Hindawi Limited, 2020)
The objective of the current study was to introduce "Polylactic co-Glycolic Acid- (PLGA-) Coated Ceramic Microparticles" as an innovative drug delivery system, loaded with a new combination of triple antibiotics (penicillin G, metronidazole, and ciprofloxacin (PMC)) for use in endodontic treatments. Ceramic microparticles were made from β-tricalcium phosphate and hydroxyapatite and examined by "Scanning Electronic Microscope (SEM)." Then, fixed amounts of the selected antibiotics were added to a prepared PLGA solution and stirred thoroughly. Next, the prepared ceramic microparticles were dispersed completely in the drugs solution. The deposited "PMC-loaded PLGA-coated ceramic microspheres (PPCMs)" were dried and incubated in phosphate buffer saline (PBS) for 21 days. The drug release from PPCMs was quantified by a UV spectrophotometer. The antimicrobial activity of PPCMs was investigated using the "Agar Plate Diffusion Test (ADT)," "Minimum Inhibitory Concentration (MIC)," and "Minimum Bactericidal Concentration (MBC)" against Enterococcus faecalis (E. faecalis) and Aggregatibacter actinomycetemcomitans (A.a). The cell viability test (MTT) was conducted for cytotoxicity against human gingival fibroblasts. SEM micrographs of PPCMs showed spherical-like ceramic microparticles with smooth surfaces. Crystal-like antibiotic particles (chunks) were also found on PPCMs. Initial burst of antibiotics (31 µg/mL, 160 µg/mL, and 18 µg/mL for ciprofloxacin, metronidazole, and penicillin G, respectively, in the first 4 days) followed by gradual and sustained release was observed within a period of 21 days. PPCMs demonstrated pH close to normal physiological environment and antibacterial activity against E. faecalis and A.a in the first 2 days. MTT showed cell viability of more than 70% for PPCMs after 24 h and 72 h of exposure. In conclusion, PPCMs demonstrated satisfactory release of antibiotics, antibacterial activity against the selected microorganisms, and biocompatibility. Thus, PPCMs may be used to deliver modified triple antibiotics to the root canal system for use in endodontic applications.